Physical properties of selected South Indian heritage paddy varieties - Veeraragavan; Priya Dharshini
There is an increasing trend in the production processing and marketing of traditional crops with a special focus on rice in the southern peninsular region of India. In this context, the current study was carried out to evaluate the dimensional, gravimetric, and frictional characteristics of selected eleven heritage paddy varieties in both raw and parboiled conditions adopting standard procedures. Among the dimensional properties, the L/B ratio classified Muttrinasannam, Thanga samba, and Basmati into an extra-long slender category with reduced volume both in the raw and parboiled conditions. In contrast, bold varieties (Mapillai samba) recorded an increase in volume both in raw and parboiled conditions. The geometric aspect ratio value recorded for Basmati was the lowest indicating good rolling properties in both the raw and parboiled conditions. The traditional rice varieties, Mapillai samba (30.18 g) and Kattuyaanam (30.03 g) scored high for thousand grain weight in raw and parboiled conditions respectively, which is a positive parameter for marketability. A strong correlation has been observed between volume with and surface area, volume with geometric mean diameter and surface area in both raw and parboiled conditions. The present study provides insights on varying post-harvest processing suitability of traditional rice varieties of south India.